Conservation of regulatory sequences and gene expression patterns in the disintegrating Drosophila Hox gene complex - Negre, Bárbara; Casillas, Sònia; Suzanne, Magali; Sánchez-Herrero, Ernesto; Akam, Michael; Nefedov, Michael; Barbadilla, Antonio; de Jong, Pieter; Ruiz, Alfredo (Genome Research, 2005)
Homeotic (Hox) genes are usually clustered and arranged in the same order as they are expressed along the anteroposterior body axis of metazoans. The mechanistic explanation for this colinearity has been elusive, and it may well be that a single and universal cause does not exist. The Hox-gene complex (HOM-C) has been rearranged differently in several Drosophila species, producing a striking diversity of Hox gene organizations. We investigated the genomic and functional consequences of the two HOM-C splits present in Drosophila buzzatii. Firstly, we sequenced two regions of the D. buzzatii genome, one containing the genes labial and abdominal A, and another one including proboscipedia, and compared their organization with that of D. melanogaster and D. pseudoobscura in order to map precisely the two splits. Then, a plethora of conserved noncoding sequences, which are putative enhancers, were identified around the three Hox genes closer to the splits. The position and order of these enhancers are conserved, with minor exceptions, between the three Drosophila species. Finally, we analyzed the expression patterns of the same three genes in embryos and imaginal discs of four Drosophila species with different Hox-gene organizations. The results show that their expression patterns are conserved despite the HOM-C splits. We conclude that, in Drosophila, Hox-gene clustering is not an absolute requirement for proper function. Rather, the organization of Hox genes is modular, and their clustering seems the result of phylogenetic inertia more than functional necessity.